Implementasi Manajemen Risiko dalam Pengelolaan Sumber Daya Pendidikan untuk Menjamin Keberlanjutan Mutu Pendidikan - Siagian Siagian; Baginda Edward; Sihotang Sihotang; Hotmaulina Hotmaulina (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the implementation of risk management in educational resource management as a strategy to ensure the sustainability of educational quality. The research method used was a qualitative approach through a Systematic Literature Review (SLR). This approach examined journal articles and proceedings published between 2020 and 2024 that were relevant to risk management, educational resource management, and quality sustainability. The selection process involved identification, screening, and quality review, resulting in 15–17 scientific articles that met the inclusion criteria. The results indicate that the implementation of risk management in human, financial, and physical resources is able to identify key threats to educational quality, such as teacher competency gaps, budget allocation inefficiencies, and the vulnerability of information technology facilities and systems. Effective mitigation strategies include teacher succession planning and professional development, risk-scenario-based budget projections, the establishment of contingency funds, and risk-based asset maintenance and digital system protection. The conclusions of this study confirm that risk management is a strategic instrument that transforms educational resource management from a reactive to a proactive approach, thus becoming a key prerequisite for ensuring the sustainability of educational quality in a systemic and sustainable manner.   Keywords: Risk Management, Educational Resources, Quality Sustainability, Enterprise Risk Management, Quality Of Education.